Job satisfaction, flexible employment and job security among Turkish service sector workers - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2013)
This article examines the association between job satisfaction, flexible employment and job security among Turkish service sector workers. Data come from a survey of workers in banking and related sectors' call centres, frontline five-star hotel staff and airline cabin crews (N = 407). Results show that flexible employment involving fixed-term contract, paid and unpaid overtime, on-call work and mismatched contract and hours are not associated with job satisfaction. Perceived job security is positively associated with job satisfaction. The study provides evidence that the perception of job security rather than flexible employment is an important contributor to job satisfaction for Turkish workers in the sample.
Keywords: Flexible employment; job satisfaction; job security; Turkish workers; CALL CENTER; ORGANIZATIONAL COMMITMENT; MARKET ECONOMIES; UNPAID OVERTIME; TEMPORARY WORK; INSECURITY; LABOR; QUALITY; STRESS; GLOBALIZATION